Diplomacy and religion - Valentan, Sebastijan (Edinost in dialog, 2025)
Based on original documents of the Protocol of the Republic of Slovenia and offering a novel, comprehensive treatment of the subject, this contribution analyses the significance of protocol visits in shaping the international relations of the Republic of Slovenia. It emphasizes that such visits are not merely formal-diplomatic events but also instruments for strengthening bilateral and multilateral ties. Particular attention is given to the rarity and prestige of state visits and to the exceptional symbolic value of Pope John Paul II’s visits, which transcended traditional protocol frameworks and reinforced Slovenia’s bond with the Holy See. The analysis shows that religion in protocol visits remains an important element of soft diplomacy, complementing political dimensions and strengthening the country’s identity in the global arena.
Keywords: diplomacija; diplomacy; diplomatic law; diplomatsko pravo; državniški obiski; international relations; mednarodni odnosi; protocol visits; protokol; protokolarni obiski; religija; religion; state visits